Workfare in an Efficiency Wage Model - Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2002)
The impacts of introducing work requirements for welfare recipients are studied in an efficiency wage model. If the workfare package is not mandatory, it will reduce employment, profits, and utility levels of employed and unemployed workers. In contrast, mandatory effort requirements will generally raise both employment and profits and reduce the tax rate. The impact on the net wage is ambiguous. Changes of utility levels of employed and unemployed workers have the same sign as the variation in the net wage. The possibility of a Pareto improvement may explain the widespread support for welfare to work experiments.
Keywords: E24; H53; I30; J41; J60; 330; workfare; welfare; efficiency wages; shirking